On Distributed Reflexive Complex Mechanisms of Decision-making in a Transportation System of a Smart city - Fedyanin, Denis; Vershinin, Yuri (International Journal of Engineering and Technology, 2018)
We describe distributed reflexive complex mechanisms of decision-making in a SMART city. These complex mechanisms are a cognitive self-organizing decision support system for development governance. These mechanisms utilize local information from all nearby sensors of city sensors on buildings, sensors on other cars, sensors on pedestrians and some additional information. We describe the way to a new level of safety of citizens by additional vision and automated reasoning.Â  It provide transparency in Augmented Reality Devices by virtually eliminating obstacles e.g. buildings. The problem is that development of a city is a process so people still have to make suggestions and now these suggestions are about awareness of other agents. Distributed reflexive complex mechanisms can assist and support their decisions in solving these problems.Â Â